Patient‐centred education: what do students think?. Issue 2 (February 2014) - Oswald, Anna; Czupryn, Joanna; Wiseman, Jeffrey; Snell, Linda
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'